2018
DOI: 10.1177/0095244318808056
|View full text |Cite
|
Sign up to set email alerts
|

Bis(isomaleimide) and diphenol blends: Non-isothermal degradation kinetics and TG-FTIR studies

Abstract: Blends of 4,4′-bisisomaleimidodiphenyl methane (VS) with structurally different diphenols are made in 1:1 molar ratio and thermally polymerized. Thermogravimetric studies of the cured materials show that the thermal stability, the degradation pattern and the char yield are much dependent on the structure of the diphenol that is used for blending. The decreased thermal stability of materials from the blends is attributed to decreased cross links owing to the opening of the isomaleimide rings by diphenols during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…In a previous study, 10,11 the thermal curing and thermal degradation behavior of pure 4,4 0 -bisisomaleimidodiphenyl methane (VS) was studied using DSC and TGA, and it was found that the addition of diphenols to VS affects the nature of the curing exotherm. The blends of VS with different diphenols were then thermally cured and their thermal stabilities were investigated using TGA.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, 10,11 the thermal curing and thermal degradation behavior of pure 4,4 0 -bisisomaleimidodiphenyl methane (VS) was studied using DSC and TGA, and it was found that the addition of diphenols to VS affects the nature of the curing exotherm. The blends of VS with different diphenols were then thermally cured and their thermal stabilities were investigated using TGA.…”
Section: Introductionmentioning
confidence: 99%